Case Report: Misdiagnosis of a lipofibromatosis-like neural tumor of the dorsal skin as dermatofibrosarcoma protuberans - Zhang, Xiaowei; Yan, Chen; Xu, Tingting; Ying, Jiajia (Frontiers in Surgery, 2024)
BackgroundLipofibromatosis-like neural tumors (LPF-NT), which have only recently been established, are intermediate soft tissue tumors with neurotrophic tropomyosin receptor kinase 1 (NTRK1) gene alterations and are typically misdiagnosed as dermatofibrosarcoma protuberans, low-grade malignant peripheral nerve sheath tumors, or spindle cell lipoma due to their histopathological and immunohistochemical expression of CD34 and S-100.Case presentationThe patient was admitted to our hospital with a painless back mass that had appeared more than 4 years prior to admission. Physical examination revealed a subcutaneous mass on the back, approximately 1.5 cm in diameter and protruding into the skin, with clear boundaries and no tenderness. The tumor was surgically resected. The postoperative pathological results suggested a spindle cell soft tissue tumor, and dermatofibrosarcoma protuberan was initially considered. After consultation at a provincial hospital, the patient was diagnosed with a cutaneous lipofibromatosis-like neural tumor of the back. A second extended resection was then performed. Intraoperative rapid freezing examination revealed negative incision margins.ConclusionHistological and immunohistochemical detections aid in the differential diagnosis of LPF-NTs. Complete surgical resection is the preferred treatment for LPF-NTs.